Profile of Patients with Chronic Obstructive Pulmonary Disease in Pulmonology Clinic, Universitas Airlangga Hospital, Surabaya, Indonesia, for the Period of January-December 2022 - I Made Dwi Yudiartana Putra Susila; Alfian Nur Rosyid; Arief Bakhtiar; Pirlina Umiastuti (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: Chronic obstructive pulmonary disease mainly occurs in male patients, elderly patients, and ex-smokers. Classification of COPD patient therapy must be chosen individually for each patient, which sometimes does not comply with existing guidelines.   Abstract Introduction: Chronic obstructive pulmonary disease (COPD) is a disease-causing breathing issue characterized by persistent and progressive airflow obstruction in response to noxious particles or gases and influenced by host factors. This study aimed to describe the profile trends, including age, sex, body mass index (BMI), complaints, physical examination findings, comorbidities, smoking history, exacerbations, COPD assessment test (CAT) score, modified Medical Research Council (mMRC) dyspnea scale, the Global Initiative for Chronic Obstructive Lung Disease (GOLD)-ABE grouping, and pharmacological therapy. Methods: Data collection included variables such as age, sex, BMI, complaints, physical examination, comorbidities, smoking history, exacerbations, CAT score, mMRC dyspnea scale, GOLD-ABE grouping, and pharmacological therapy. Results: A total of 73 patients were included. The sample was dominated by male patients (84.93%), aged 61-70 years old (38.35%), had normal BMI (63.01%), most complained of persistent cough (57.53%), had normal physical examination (97.26%), had no comorbidities (82.19%), ex-smokers (63.01%), and had no exacerbations (39.72%). Most were classified as Group B (50.68%) in the GOLD-ABE Group, medium (54.79%) on the CAT Score, and grade 1 (42.47%) on the mMRC dyspnea scale. Most patients were treated with long-acting β2-agonist (LABA)+inhaled corticosteroid (ICS) (79.45%) and with mucolytics (27.40%). Conclusion: Chronic obstructive pulmonary disease predominantly affected elderly male patients, especially aged 61-70 years old, with a history of smoking. Most had a normal BMI, reported persistent cough, and had no comorbidities. Patients were primarily classified under GOLD-ABE Group B with moderate symptoms, while severe exacerbations were rare. Treatment mainly involved LABA+ICS combinations, though adherence to updated guidelines varied. Further research is needed to refine treatment strategies and to explore additional variables to improve management.